Ethical realism and the Darwinian Dilemma - Rabinowitz, Aaron, author; Tropman, Elizabeth, advisor; MacKenzie, Matthew, committee member; Hickey, Matthew, committee member (Colorado State University. Libraries, 2012)
In this thesis, I will examine a recent objection against ethical realism put forth by Sharon Street, a prominent advocate of ethical constructivism. Street's Darwinian Dilemma argues that ethical realism is incompatible with evolutionary psychology and that attempts to reconcile the two theories will result in the unacceptable epistemic conclusion that humans lack ethical knowledge. Street believes that the Darwinian Dilemma provides a strong reason for abandoning ethical realism in favor of ethical constructivism. It is my contention that the ethical realist can successfully defend herself against Street's objection. I will consider several possible responses that are available to the ethical realist for defusing the Darwinian Dilemma, including my preferred response which I believe has largely been neglected in the literature. I will argue that these responses provide the ethical realist with a functional defense against Street's challenge, and that ethical realism therefore remains superior to ethical constructivism.
Keywords: Darwinian; Street; realism; ethics